The Regeneration of Ammonia Solution by Calcium Hydroxide for Carbon Dioxide Absorption from the Flue Gas - Hsin Ta Hsueh; Tsung Wen Chien; Tzu Hsing Ko; Teng Te Huang; Hsin Chu (The Global Environmental Engineers, 2015)
The tests of this study were conducted by the semi-continuous flow experiments to absorb the carbon dioxide (CO2) gas in a bench-scale spraying column reactor. The absorption capacity and the regeneration efficiency of the absorbed ammonia (NH3) solution were determined. In this study, the maximum regeneration efficiency is 68.4% as the concentration of NH3 solution is 1% and the ratio of calcium hydroxide (Ca(OH)2) and CO2 is 1 as well. Furthermore, the absorption capacity of the NH3 solution decreases from 1.67 to 0.27 kg-CO2/kg-NH3 after regenerating four times due to the 30-38% loss each time. Regarding the regeneration kinetics between absorbed products and Ca(OH)2, the comparative degree of covered Ca(OH)2 during the reaction was recognized after fitting by a surface coverage model. Finally, the ammonium bicarbonate (NH4HCO3) reduced by Ca(OH)2 to calcium carbonate (CaCO3) solid and NH3 solution in the regeneration reactions was observed by scanning electron microscope (SEM), Energy-dispersive X-ray spectroscopy (EDS) pictures and X-Ray Diffraction (XRD) analyses. Although the NH3 solution can be regenerated by Ca(OH)2 effectively in this study, the overall benefit of this process should be estimated further in the energy aspect.